PERBAIKAN KUALITAS PRODUKSI DENGAN MEMPERTIMBANGKAN FAKTOR-FAKTOR DOMINAN (STUDI KASUS PADA PT. “X’’ DI KOTA AMBON) - Novita Irma Diana Magrib (Prodi Teknik Industri Universitas Muhammadiyah Gresik, 2018)
Nowadays, along with the development of human civilization, there are modern companies which appear in numbers. It happens because of the development of technology and people’s skills as well. It is obviously will influence the production process and implementation. And, in fact, there are some companies whose production outcomes are the same with the other ones. Consequently, they compete to each other. In this thesis writing, the writer prefers the research on the effort of production quality improvement of physical. The Analysis is done with the helping tools of quality control. The tools used are (1) Control Chart P, is to measure the incompatibility for it does not support the specification (it is often called disabled parts) of some items in a group/subgroup which is being checked; (2) Pareto Diagram, is to interpret problems of any levels; (3) Cause an Effect Diagram, is to show cause factors and quality characteristic which is caused by those factors. The use of helping tools of quality control is chosen so as to the number and the cause of damages can be figured-out and handled early and properly. Based on the calculation Control Chart P, the product proportion which is rejected before the prevention is 8,34% from the total number of the disabled ones. On the contrary, the product proportion after the prevention is 5,75%. It shows that there is reduction, that is 31,06% compared to the previous prevention.